Intravitreal Bevacizumab Injection Attenuates Diabetic Retinopathy in Adult Rats with Experimentally Induced Diabetes in the Early Stage. (9th May 2018) - Lv, Jiao; Chen, Miao-Miao; Mu, Zhi-Hao; Wang, Fang; Qian, Zhong-Yi; Zhou, Lei; Guo, Qiu-Ting; Zhao, Zhi-Min; Pan, Yu-Ping; Liao, Xin-Yu; Yang, Zhi-Hong; Cai, Ning; et al.
Abstract : Diabetic retinopathy is the leading cause of blindness, yet its treatment is very limited. Anti-VEGF drug has been widely applied in ocular disease, but its effects on diabetic retinopathy and the underlying mechanism have remained to be fully explored. To elucidate the role of anti-VEGF treatment, we sought to determine the effects of bevacizumab on diabetic neurovascular changes extending from the 3rd to 9th week with induced diabetes in adult rats. The retinal neurovascular changes included increased expression of VEGF, nNOS, iNOS, eNOS, and NO in the course of diabetes progression. In diabetic rats given bevacizumab injection, the ganglion cell loss and alterations of retinal thickness were ameliorated. In this connection, the immunofluorescence labeling of the above biomarkers was noticeably decreased. Along with this, Western blotting confirmed that bevacizumab treatment was associated with a decrease of VEGF, Flk-1, and cAMP response element binding and protein kinase C protein expression. The present results suggest that bevacizumab treatment in the early stage of the retinopathy may ameliorate the lesions of retinopathy, in which VEGF/Flk-1 signaling has been shown here to play an important role.